2022
DOI: 10.3390/ani12233251
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in Performance of Nursery Pigs Provided with Supplemental Oil Derived from Black Soldier Fly (Hermetia illucens) Larvae

Abstract: The current study evaluated the impact of increasing levels of supplemental black soldier fly larvae (BSFL) oil, a novel and sustainable feed ingredient, on growth performance and blood chemistry indices in nursery pigs. Pigs were weaned at 21 days of age (n = 192; body weight = 6.9 ± 0.15 kg) and randomly allotted within sex and body weight to 1 of 4 dietary treatments, using 48 pens (4 pigs/pen). Treatments contained 0, 2, 4, or 6% supplemental BSFL oil, replacing equivalent quantities of corn oil. A 3-phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
0
0
Order By: Relevance
“…In our experiment, the supplementation of feed with 2.5 or 5% HI meal (36.5 g of lauric acid per 100 g of all estimated acids) did not influence the cholesterol content in the blood. In contrast, in the experiment by van Heugten et al (2022) [34] where the HI larvae oil (36.5-37.3 g of lauric acid/100 g) was used in the amount of 2%, 4%, or 6% in the feed, the increase in total cholesterol level (by about 17% compared to control group) was the only significant effect observed in piglets' biochemical blood indices. These authors, however, did not notice any effect of lauric acid present in HI oil on the hematological parameters.…”
Section: Blood Indicesmentioning
confidence: 79%
See 1 more Smart Citation
“…In our experiment, the supplementation of feed with 2.5 or 5% HI meal (36.5 g of lauric acid per 100 g of all estimated acids) did not influence the cholesterol content in the blood. In contrast, in the experiment by van Heugten et al (2022) [34] where the HI larvae oil (36.5-37.3 g of lauric acid/100 g) was used in the amount of 2%, 4%, or 6% in the feed, the increase in total cholesterol level (by about 17% compared to control group) was the only significant effect observed in piglets' biochemical blood indices. These authors, however, did not notice any effect of lauric acid present in HI oil on the hematological parameters.…”
Section: Blood Indicesmentioning
confidence: 79%
“…There were no differences in average daily feed intake among all three groups. One study [34] was conducted for 40 days to investigate the effect of increasing levels of HI larvae oil supplementation on the growth performance of newly weaned pigs (at 21 days of age) reared in a three-phase feeding program. It was found that supplementation with 0%, 2%, 4%, or 6% of insect oil linearly increased (p < 0.05) body weight on days 14, 21, 25, 33, and 40, but did not affect the feed intake throughout the whole experiment.…”
Section: Growth Performancementioning
confidence: 99%